Faculty Development Effectiveness: Insights from a Program Evaluation. (23rd June 2014) - Wadhwa, Anupma; Das, Lopamudra; Ratnapalan, Savithiri
Abstract : Background. Faculty development programs are often time and resource intensive. In order to accommodate time constrained clinicians a limited time commitment faculty development program was developed and was shown to be effective in improving participant's scholarly productivity. Objectives . The objective of this study was to assess participants' perceptions of why the faculty development program was effective in promoting scholarship in education. Methods . In-depth semistructured interviews of course participants were conducted a year after completing a faculty development program. The interviews were audiotaped and transcribed verbatim. The transcriptions were coded independently by the investigators for dominant themes. The investigators held coding meetings to further refine the themes and discrepancies were handled by referring to the transcripts and reaching consensus. Results . The participants' satisfaction with the course as described in the interviews correlated with the early satisfaction surveys. Reasons offered for this impact fell into four broad categories: course content, course format, social networking during the course, and the course facilitation coaching strategies to achieve goals. Conclusions. Course focusing on the process, experiential learning, and situating the course facilitator in the role of a functional mentor or coach to complete projects can be effective in facilitating behaviour change after faculty development programs.